Axiological dimensions of medical deontology in pediatric surgery - V.O. Dubinina; I.V. Ksonz; S.M. Bilash; L.V. Abyzova; O.S. Bilanov; V.I. Ksonz (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
The achievements of contemporary medicine, application of advanced technologies and comprehensive therapeutic and diagnostic investigations are not limited to broadening the range of professional opportunities for pediatric surgeons but also require further rationalization of the axiological discourse of medical deontology. Purpose. The article aims at theoretical and methodological substantiation of the axiological principles of medical deontology in pediatric surgery. The theoretical and methodological foundation of the scientific research includes the theory of creative development and self-improvement of an individual, the theory of education and personal development in changing socio-cultural conditions, concepts of humanization of education, conceptual approaches to the general theory of activity and philosophical theories of values. The professional activities of medical workers in pediatric surgery inevitably include the process and result of a deontological dominant, manifested in the profound understanding by the medical experts of their professional and human duties, and in a high moral and ethical responsibility for the quality of their professional activities. Conclusions. Philosophy and axiology constitute the worldview and methodological basis of medical deontology, particularly in surgery. The genesis of knowledge about moral and ethical principles and the professional duty of a pediatric surgeon is presented in the form of a logical chain: philosophy - axiology - deontology - medical deontology - deontology in surgery - deontology in pediatric surgery. The process of forming the deontological competence of medical professionals in pediatric surgery will be successful if the organization of deontological training for future healthcare providers is based on principles of humanism, in compliance with the requirements of the social environment, and implemented in the educational process through a productive mechanism. No conflict of interests was declared by the authors.